Rape and the Querela in Italy: False Protection of Victim Agency - Van Cleave, Rachel A. (2007)
This Essay describes the history of the querela in Italy and explores the controversy surrounding the decision to maintain this institution. In addition, this Essay questions the degree to which the querela can protect victim agency when the attitudes of judges and lawyers in the Italian criminal justice system reflect persistent rape myths